Prediction of Severity of Anxiety, Depression and Obsession Symptoms based on Negative Repetitive Thoughts by Mediating Role of Experimental Avoidance in Clinical Populations Referring to Counseling Centers in Tehran - Zaranat, Maryam; Sahragard, Mahdi (International Journal of Applied Behavioral Sciences, 2023)
Background and Aim:A deep understanding of the effective factors in creating and aggravating the symptoms of anxiety, depression and obsession is very vital for the development of treatment and prevention strategies, and also repeated negative thoughts can play an important role in the process of forming and strengthening these symptoms, and on the one hand, empiricism and avoidance of unpleasant experiences may also act as an effective mediating variable in these processes So. the present study was done to predict severity of anxiety, depression and obsession based on negative repetitive thoughts by mediating role of experimental avoidance in clinical population who are all male and femalewith anxiety and obsession disorders in 2023 in Tehran. Materials and Methods:This was a descriptive correlation research in which structural equations were done on 228 male and female participants with anxiety, depression and obsession disorders were selected by available sampling by Kline method. to collect data, Spielberger state-trait anxiety inventory (STAI), Beck depression inventory, repetitive thought questionnaire and obsession compulsive questionnaire of Maudsely (MOCL) were used. Results:Findings suggested that by increasing negative repetitive thoughts and experimental avoidance, anxiety, depression and obsession will be increased or vice versa. by decreasing negative repetitive thoughts and experimental avoidance, anxiety, depression and obsession will be decreased. Also, given to GFI=0/909, CFI=0/919, AGFI=0/837 and RMSEA=0/076 it can be said that measured model has good fitness. Conclusion:According to results, severity of anxiety, depression and obsession are predictable based on negative repetitive thoughts. Because anxiety is caused by trying to control or resist unwanted negative thoughts that occur normally, also because OCD is a chronic anxiety disorder characterized by excessive mental preoccupation with subjective details and perfectionism. is, to the extent that it leads to the loss of flexibility and social function, and depression, which is the constant and continuous tendency of a person to experience uncomfortable thoughts and feelings, it is possible to predict the severity of symptoms of anxiety, depression and obsession based on negative thoughts and repetition Shundeh is concerned with the avoidance and direct efforts he made to get rid of a negative thought or emotion So, using strategies for control negative repetitive thoughts for improving mental health and decreasing anxiety and depression and obsession are necessary.